The impact of green finance on green economy development efficiency: based on panel data of 30 provinces in China - Liu, Donglan; Chang, Yingxian; Yao, Honglei; Kang, Yuxin (Frontiers in Environmental Science, 2023)
Within the framework of China's socioeconomic transition from a phase of rapid growth to one of high-quality development, it becomes crucial to focus on advancing the green economy to sustain economic progress. Green finance plays a pivotal role in underpinning green industries and fostering the progression of a green economy. Under the auspices of green finance, social capital is increasingly directed towards industries that prioritize energy efficiency, low carbon emissions, and environmental friendliness, thereby spurring technological innovation and industrial metamorphosis in businesses. In this paper, data envelopment approach (DEA) is used to measure the green economic development efficiency of 30 Chinese provinces from 2008 to 2018 in general and by sub-region. The two-way fixed-effects model (Two-way FE) and difference-in-difference (DID) model are established to empirically analyze the effect of green finance on green economy development efficiency and the influence of green polices on these two, with sub-region models examining the heterogeneity of this impact in eastern, western and central regions. The findings suggest that green finance significantly enhances a positive influence on green economic development efficiency, albeit with regional variations. Furthermore, the implementation of green policies facilitates green finance and green economic development.